Las revistas culturales y la integración de Nuestra América. - Véjar Pérez-Rubio, Carlos (2014)
The Latin American and Caribbean cultural magazines have always played a prominent role in social development and integration of our peoples. In fact, culture is the spearhead of integration, the front vertex of a triangle closed for the economy and politics. This is the theory of the spearhead. The aggregation of knowledge is the conceptual basis underlying this paper, which outlines and discusses some of the most significant journals that have existed in the area of our Americas, and the commitment of their creators and collaborators.